First clinical real-time motion-including tumor dose reconstruction during radiotherapy delivery. (October 2019) - Skouboe, Simon; Ravkilde, Thomas; Bertholet, Jenny; Hansen, Rune; Worm, Esben Schjødt; Muurholm, Casper Gammelmark; Weber, Britta; Høyer, Morten; Poulsen, Per Rugaard
Highlights: World's first motion-including dose calculation during clinical treatment delivery. Real-time dose calculation to a moving tumor during radiotherapy in the liver. Motion-induced dose errors can be calculated accurately on-the-fly during treatment. An important step from unmonitored treatments to in-treatment tumor dose monitoring. Abstract: Purpose: To clinically implement and characterize real-time motion-including tumor dose reconstruction during radiotherapy delivery. Methods: Seven patients with 2–3 fiducial markers implanted near liver tumors received stereotactic body radiotherapy on a conventional linear accelerator. The 3D marker motion during a setup CBCT scan was determined online from the CBCT projections and used to generate a correlation model between tumor and external marker block motion. During treatment, the correlation model was updated by kV imaging every three seconds and used for real-time tumor localization. Using streamed accelerator parameters and tumor positions, in-house developed software, DoseTracker, calculated the dose to the moving tumor in real-time assuming water density in the patient. Post-treatment, the real-time tumor localization was validated by comparison with independent marker segmentations and 3D motion estimations. Dose reconstruction was validated by comparison with treatment planning system (TPS) calculations that modeled motion as isocenter shifts and used both actual CT densities and water densities. Results: The real-time estimated tumor position had a mean 3D root-mean-square error of 1.7 mm (range: 0.9–2.6 mm). The motion-induced reduction in the minimum dose to 95% of the clinical target volume (CTV D95) per fraction was up to 12.3%-points. It was estimated in real-time by DoseTracker during patient treatment with a root-mean-square difference relative to the TPS of 1.3%-points (TPS CT) and 1.0%-points (TPS water). Conclusions: The world's first clinical real-time motion-including tumor dose reconstruction during radiotherapy was demonstrated. This marks an important milestone for real-time in-treatment quality assurance and paves the way for real-time dose-guided treatment adaptation.